Acoustic signals associated with the passage of penetrating cosmic radiation through a seismically stressed environment - Zhukov, V.V.; Idrisova, T.K.; Mukashev, K.M.; Muradov, A.D.; Sadykov, T.Kh.; Saduyev, N.O.; Umarov, F.F.; Shepetov, A.L. (Recent Contributions to Physics, 2020)
We detected the sporadic acoustic pulses presumably connected with the processes of seismic activity in the region of a deep earth’s crust fracture near Almaty city. It was found a statistically significant time correlation between such pulses and the passage moments of high energy cosmic ray muons. This observation is in favor of a theoretic supposition about possible trigger effect of small ionization created by penetrative particles deep underground which may provoke releasing the energy of elastic deformation accumulated at the edges of a seismic fault. If confirmed, this effect could be of interest for the earthquake forecast problem. Such complex experiments can be carried out at the Tien Shan high-mountain scientific station. The station is located at an altitude of 3340m above sea level near the city of Almaty in a seismically active region. The station is equipped with a wide network of detectors to register extensive air showers of cosmic radiation. These showers are the source of high energy muons. The network consists of 72 scintillation detectors and covers an area of 1000 m2. A special high-sensitivity microphone sensor is used to detect and register acoustic signals. The sensor is placed in a borehole at a depth of 50 m, not far from the axis of extensive air showers. The passage of the muon component of cosmic rays can still be judged by the response of neutron detectors. These detectors are located underground at a depth of 20 m water equivalent. A statistically significant correlation was found between the times of passage of high-energy cosmic ray muons and the subsequent appearance of acoustic events.